Ontogeny of the intestinal immune system (Hematology Meeting Reports, 2009)
All major components of the gut immune apparatus including the (1) epithelial barrier (2) mononuclear leukocytes in the lamina propria, and (3) organized gut-associated lymphoid tissue are anatomically identifiable in the fetus by 200 days of gestation. However, the functional maturation of this mucosal immune system is completed only in the postnatal period following introduction of enteral feeds and colonization with commensal bacterial flora. In the premature or sick newborn infant, this process of maturation might be delayed or altered and may in turn predispose the infant to infection, inflammatory states such as necrotizing enterocolitis, and allergic sensitization.